2018
DOI: 10.1021/acsphotonics.8b01141
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic High-Contrast Grating Based Polariton Laser

Abstract: High-reflectance gratings promise new generations of vertical-cavity lasers that allow flexible control of the lasing mode properties and better integration. To date, conventional and polariton vertical-cavity lasers have been created with high-contrast gratings surrounded by air. Suspended in air, these gratings are delicate to fabricate and use, and are difficult for precise property control, electrical injection or thermal management. Here, we demonstrate a high quality vertical-cavity laser with a nonsuspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…A schematic of the SWG-based microcavity is shown in Fig. 1a It has been shown that an SWG made of straight, periodic bars can function as a polarization-selective mirror with high enough reflectance to support polariton lasing [28,29]. This is because the guided wave resonances in the grating are polarized parallel or perpendicular to the grating; they can be designed to interfere at the surface of the grating to allow nearly perfect reflectance for one of the polarizations, while the orthogonally polarized mode has low reflectance [30][31][32][33].…”
Section: Setup and Principle Of The Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…A schematic of the SWG-based microcavity is shown in Fig. 1a It has been shown that an SWG made of straight, periodic bars can function as a polarization-selective mirror with high enough reflectance to support polariton lasing [28,29]. This is because the guided wave resonances in the grating are polarized parallel or perpendicular to the grating; they can be designed to interfere at the surface of the grating to allow nearly perfect reflectance for one of the polarizations, while the orthogonally polarized mode has low reflectance [30][31][32][33].…”
Section: Setup and Principle Of The Experimentsmentioning
confidence: 99%
“…1b) with diameters up to 8.65 µm. The grating parameters are optimized to have high reflectivity only for light polarized perpendicular to the grating bars (transverse-magnetic, TM) incident from the cavity [28], including a grating period of about 336 nm and a duty cycle, defined as the ratio of the width of the high-index material to the period, of about 0.7.…”
Section: Setup and Principle Of The Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our numerical findings were confirmed by experimental characterization of the power reflectance spectrum [18] of a stand-alone MHCG fabricated from GaAs and designed for a wavelength of 980 nm. In [19], Kim et al reported first MHCG-cavity polariton laser and later we showed the first electrically-injected MHCG VCSEL with peak emission wavelengths of 980 nm and continuous wave lasing up to 75 C [20].…”
Section: Introductionmentioning
confidence: 99%